Follow-up care for cancer survivors: the views of clinicians - Greenfield, D M (Nature Publishing Group, 2009)
BACKGROUND: Evidence for the efficacy of late effects surveillance in adult cancer survivors is lacking and there is little agreement among clinicians on appropriate follow-up care. METHODS: We report the views of both cancer experts and general practitioners (GPs) on long-term follow-up provision for cancer survivors, focussing on the 18–45 years age group. A total of 421 cancer experts (36% haematologists, 33% oncologists, 18% surgeons, 10% nurses, 2% other) and 54 GPs responded to a structured online survey. Reasons for follow-up care (clinical or supportive); advantages and disadvantages of follow-up in primary care; current practice; and resources required for a quality follow-up service were assessed. RESULTS: Clinicians valued clinical reasons for follow-up more highly than supportive reasons (P<0.001). Learning more about late effects and checking for cancer recurrence were rated as the most important reasons for follow-up by cancer experts and GPs. A total of 85% of cancer specialists hold follow-up consultations alongside patients on active treatment. Cancer experts agreed that primary care follow-up would increase their availability for acute oncological care, but reduce information on late effects. The most important resource to provide a quality follow-up service was specialist nursing support (91%). CONCLUSIONS: Follow-up guidelines that include late effects surveillance are needed. Where and who should deliver this care requires further debate.